Vertical osteoconductivity and early bone formation of titanium-zirconium and titanium implants in a subperiosteal rabbit animal model - Kämmerer, Peer Wolfgang; Hagmann, Sébastien (Clinical oral implants research, 2014)
Objectives The aim of this pilot study was to evaluate the vertical osteoconductive and osteointegrative dynamics around titanium-zirconium (TiZr) implants compared to titanium (Ti) implants. Materials and methods In a split-leg design, 12 TiZr-SLActive and 12 Ti-SLActive implants were inserted 3 mm above bone level in the proximal tibia of 12 rabbits. Full periosteal flaps were repositioned to cover the site. Specimens were obtained after 10, 20 and 30 days (each n = 4 per group). Histomorphometric measurements included percentage of linear bone fill (PLF; %), new marginal vertical bone height (VBH; mm) and vertical bone-to-implant contact (vBIC; %). Statistical analysis was performed with the nonparametric F1_LD_F1 model to compare the two groups at the different time points. Results After 10 days, mean PLF was 7.7% (standard deviation (SD): 5.3) for TiZr and 17.6 (SD: 8.3) for Ti. Mean VBH was 0.35 mm (SD: 0.15) and 0.78 mm (SD: 0.4) for TiZr and Ti, respectively; mean vBIC was 24.4% (SD: 41) for TiZr and 53% (SD: 28.9) for Ti samples. The differences were significant for all parameters (PLF: P = 0.021; VBH: P = 0.009; vBIC: P = 0.011). After 20 days, mean PLF was 44.3% (SD: 26.3) for TIZr and 46.2% (SD: 21.3) for Ti implants. TiZr showed a mean VBH of 1.73 mm (SD: 1) and 1.8 mm (SD: 0.6) for Ti samples. Mean vBIC had values of 48.3% (SD: 23.7) and 68.7% (SD: 35.5) for TiZr and Ti, respectively (PLF: P = 0.78; VBH: P = 0.58; vBIC: P = 0.47). At the point of 30 days, mean PLF values were 23.7% (SD: 3.8) for TiZr and 28.9% (SD: 21.7) for Ti samples; mean for VBH in TiZr samples was 0.65 mm (SD: 0.39) and 1.7 mm (SD: 1.1) for Ti ones. Finally, mean vBIC was 28.3% (SD: 19.3) and 54.4% (SD: 26.5) for TiZr and Ti samples, respectively (PLF: P = 0.1; VBH: P = 0.088; vBIC: P = 0.089). Conclusions A significant delay in vertical osteoconductivity at the earliest time point under examination was seen for TiZr implants when compared to their Ti counterparts. For the later points, TiZr as well as Ti implants demonstrated comparable values in this animal model. The long-term osteogenic surface properties of equally pretreated TiZr dental implants are therefore similar to those of Ti implants in vivo.